2010
DOI: 10.1590/s0004-282x2010000600012
|View full text |Cite
|
Sign up to set email alerts
|

The neurological examination of non-complicated preterm newborns using the Saint-Anne Dargassies Scale from birth to term

Abstract: Objective: To describe the maturational development of 20 (aged 32-36 weeks) premature newborns (PNBs) without clinical or neurological complications from birth until term. Method: The Saint-Anne Dargassies Scale was applied every two weeks until the age of 37 weeks. Results: The PNBs showed normal Apgar and the growth in head circumference was adequate for postmentrual age. The Friedman ANOVA test found a significant difference only for the heel-to-ear angles from birth until term. The Saint-Anne Dargassies S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…This was in accordance with previously published studies though the timing of examination differed in these studies from the present study. [ 18 19 20 21 22 ] One study observed muscle tone assessment of preterm infants not to be influenced by birth weight, and the evolution is clearly related to PCA.…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with previously published studies though the timing of examination differed in these studies from the present study. [ 18 19 20 21 22 ] One study observed muscle tone assessment of preterm infants not to be influenced by birth weight, and the evolution is clearly related to PCA.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the infants' articular angles (A), a goniometer was specially adapted, per Alves and Melo. 21 At the end of each item assessed by the SDS, the score values between 0 and 2 were estimated, where 0 was an absent response, 1 an altered response and 2 an expected response.…”
Section: Methodsmentioning
confidence: 99%